2018
DOI: 10.14419/ijet.v7i3.18.16665
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Otsu’s Thresholding-Based Retinal Blood Vessel Segmentation for Detection of Retinopathy

Abstract: Retinal blood vessel segmentation is crucial as it is the earliest process in measuring various indicators of retinopathy sign such as arterial-venous nicking, and focal arteriolar and generalized arteriolar narrowing. The segmentation can be clinically used if its accuracy is close to 100%. In this study, a new method of segmentation is developed for extraction of retinal blood vessel. In this paper, we present a new automated method to extract blood vessels in retinal fundus images. The proposed method compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The obtained performance of the proposed algorithm was compared with the human observers and the other existing vessel diameter quantification method (see Table 3). In the stage of segmentation it was observed that for the noisy and high‐resolution images, the applied thresholding‐based ISODATA [28] segmentation method provided more accurate results in comparison with other existing segmentation methods such as the morphological and Otsu's thresholding method [6]. The resultants of the proposed algorithm appeared as pixel values with a decimal point because these were calculated as the mean of pixel values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained performance of the proposed algorithm was compared with the human observers and the other existing vessel diameter quantification method (see Table 3). In the stage of segmentation it was observed that for the noisy and high‐resolution images, the applied thresholding‐based ISODATA [28] segmentation method provided more accurate results in comparison with other existing segmentation methods such as the morphological and Otsu's thresholding method [6]. The resultants of the proposed algorithm appeared as pixel values with a decimal point because these were calculated as the mean of pixel values.…”
Section: Discussionmentioning
confidence: 99%
“…Y K3 ), … and (X Kn , Y Kn ) are the coordinates of K 1 , K 2 , K 3 , … Kn pixels. Then the mean ED, the radius of the ROI can be computed following (6) (see (6)) . Fig.…”
Section: Vessel Diameter Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The process was dependent on the threshold value (U) to fix which areas were included into foreground and which areas were included into background. To create a binary image, the image binarization process was as followed [27]:…”
Section: Segmentationmentioning
confidence: 99%